1988
DOI: 10.1007/bf00046846
|View full text |Cite
|
Sign up to set email alerts
|

Litter production and nutrient cycling in coffee (Coffea arabica) or cacao (Theobroma cacao) plantations with shade trees

Abstract: The relative importance of N fixation, organic material inputs and nutrient inputs in litterfall, as justifications for including shade trees in plantations of coffee or cacao, is discussed. According to existing data, N fixation by leguminous shade trees does not exceed 60kg.N/ha/a. However, these trees contribute 5,000-10,000kg. organic material/ha/a.Comparisons are made between the leguminous shade tree Erythrina poeppigiana and the non-leguminous timber tree Cordia alliodora. The former, when pruned 2 or 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
2
13

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 18 publications
4
75
2
13
Order By: Relevance
“…Rangel et al (2008), while assessing the input of plant residues in coffee crops, observed a decrease in soil loss through erosion and an increase in soil organic carbon due to less soil tilling. Beer (1998) reported soil accumulation of up to 14 Mg ha -1 per year of residues originating from fallen leaves and pruned material, in dense coffee cropping. Aquino et al (2008a), who evaluated earthworm populations in agroforestry systems with conventional and organic coffee crops, found lower earthworm density under full sun and that shading from Erythrina favored earthworm diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Rangel et al (2008), while assessing the input of plant residues in coffee crops, observed a decrease in soil loss through erosion and an increase in soil organic carbon due to less soil tilling. Beer (1998) reported soil accumulation of up to 14 Mg ha -1 per year of residues originating from fallen leaves and pruned material, in dense coffee cropping. Aquino et al (2008a), who evaluated earthworm populations in agroforestry systems with conventional and organic coffee crops, found lower earthworm density under full sun and that shading from Erythrina favored earthworm diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Others have focused on the relationships between types or diversity of shade tree species and nutrient and organic matter content of soils (Mogollón et al 1997;Romero-Alvarado et al 2002;Siebert 2002). Yet other studies have examined the relationship in shade coffee between specific management practices and soil characteristics, such as organic matter content, soil aggregation and nutrient content from shade tree residues (Beer 1988;Mendoca and Stott 2003;Hoyos and Comerford 2005;Payan et al 2007;Teklay 2007), weed and mulch management (Afrifa et al 2003;Sarno et al 2004;Watanabe et al 2007). Although we know from other systems that plant species composition can have significant impacts on availability and recycling of key nutrients in agroecosystems (Leblanc et al 2007;Redel et al 2007), and greater plant species diversity can increase nutrient use efficiency and reduce nutrient leaching (Tilman et al 1996;Schroth et al 2001), there has been little work on interactions between the agroecosystem properties of shade coffee systems and their collective impact on soil characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Soil pH decreases when forest soils are turned over to perennial crops, such as coffee and cocoa (Beer, 1988;Beer et al, 1998;Hartemink, 2005). Lowering soil pH decreases the availability of basic cations, particularly Ca and Mg.…”
Section: Nutrients Removed (Kg Hamentioning
confidence: 99%
“…However, they also provide inputs of nutrients to the system through leaf litter or by nitrogen-fixation. In Central America, Cordia alliodora shade trees on each hectare of coffee produce 5.7 tons of leaf litter per year, containing 114 kg N, 7 kg P and 54 kg K (Beer, 1988). Forest trees providing shade for cocoa in West Africa produced 5 tons of leaf litter per hectare each year, containing 79 kg N and 4.5 kg P (Murray, 1975).…”
Section: Shade and Nutritionmentioning
confidence: 99%
See 1 more Smart Citation